2000
DOI: 10.1046/j.1460-9568.2000.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in the hippocampus of patients with temporal lobe epilepsy display changes in potassium conductances

Abstract: Functional properties of astrocytes were investigated with the patch-clamp technique in acute hippocampal brain slices obtained from surgical specimens of patients suffering from pharmaco-resistant temporal lobe epilepsy (TLE). In patients with significant neuronal cell loss, i.e. Ammon's horn sclerosis, the glial current patterns resembled properties characteristic of immature astrocytes in the murine or rat hippocampus. Depolarizing voltage steps activated delayed rectifier and transient K+ currents as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
186
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 255 publications
(210 citation statements)
references
References 54 publications
15
186
2
7
Order By: Relevance
“…This may lead to an increase of glutamate in astrocytes resulting in its excessive release, triggering synchronized depolarization of groups of neurons, or paroxysmal depolarization shifts (Tian et al, 2005). Reactive astrocytes have also been shown to downregulate inward rectifying K ϩ channels (Kir), specifically Kir4.1, in posttraumatic and temporal lobe epilepsy, leading to impairment of clearance of extracellular K ϩ , linked to neuronal hyperexcitability (Bordey and Sontheimer, 1998;Heinemann et al, 2000;Hinterkeuser et al, 2000;Schroder et al, 2000). In addition, aquaporin-4, the major water channel, loses its polarized location in astrocytic endfeet and becomes distributed across the entire cell body, potentially contributing to abnormalities of both water homeostasis and K ϩ buffering (Eid et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to an increase of glutamate in astrocytes resulting in its excessive release, triggering synchronized depolarization of groups of neurons, or paroxysmal depolarization shifts (Tian et al, 2005). Reactive astrocytes have also been shown to downregulate inward rectifying K ϩ channels (Kir), specifically Kir4.1, in posttraumatic and temporal lobe epilepsy, leading to impairment of clearance of extracellular K ϩ , linked to neuronal hyperexcitability (Bordey and Sontheimer, 1998;Heinemann et al, 2000;Hinterkeuser et al, 2000;Schroder et al, 2000). In addition, aquaporin-4, the major water channel, loses its polarized location in astrocytic endfeet and becomes distributed across the entire cell body, potentially contributing to abnormalities of both water homeostasis and K ϩ buffering (Eid et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, although both types are found in the nonsclerotic hippocampi from TLE patients, they report an almost complete loss of GluT cells in the CA1 region of the sclerotic hippocampus. 35 Furthermore, it was the GluR cells in the sclerotic tissue but not in the nonsclerotic hippocampus that had increased levels of the Flip isoform of GluR1. 14 …”
Section: Figmentioning
confidence: 97%
“…33,34 A third study found no increase. 35 The expression of voltage-dependent calcium channel a 1 subunits was examined by immunohistochemistry in sclerotic hippocampi from patients with TLE and compared to their expression in autopsy controls. 36 A signif-…”
Section: Membrane Ion Channelsmentioning
confidence: 99%
See 2 more Smart Citations